The Toxicity of Lanthanum and Cerium in Conditions of Biotest with Allium cepa - A. D. Kotelnikova; I. A. Fastovets; O. B. Rogova; V. V. Stolbova (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The influx of rare-earth elements into the soil is associated with ecological risks. The absence of regulatory standards for these elements in the environment makes it necessary to assess their impact on the biota. The use of biotests may be helpful not only in revealing potential integral toxicity according to the changes in growth indices, but also in characterizing the impact of the studied agent on the genetic apparatus of test object cells. In this study we used the test system with bulb onion ( Allium cepa L.) to сharacterize integral phytotoxicity, and also cyto- and genotoxicity of lanthanum and cerium chlorides. The following lanthanum concentrations were tested: 0 (control), 2, 5, 10, 30 and 50 mg/l. A significant decrease in the proportion of dividing cells (mitotic index) for all of the investigated concentrations of lanthanum was shown, and cerium was found to decrease mitotic index at concentrations 5 mg/l and higher. The frequency of mitosis pathologies was significantly higher compared to the control group for lanthanum and cerium at concentration 50 mg/l, which suggests possible genotoxicity of these rare earth elements. The decrease in mitotic index was accompanied by inhibited onion root elongation in biotests with both lanthanum and cerium.